2002
DOI: 10.1002/1521-3951(200212)234:3<769::aid-pssb769>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Polarization Charge-Induced Asymmetry of I-V Characteristics of AlN/GaN-Based Resonant Tunnelling Structures

Abstract: PACS: 73.40.Gk; 73.61.Ey Numerical simulations of AlN/GaN-based resonant tunnelling diode structures are presented, employing self-consistent real-time Green's functions. The simulated current-voltage characteristics show strong asymmetry effects due to polarization charges at the heterointerfaces in the doublebarrier region.Introduction During the last decade there has been tremendous progress in semiconducting III-nitride material science and technology. Early, very successful device applications in the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…The observed asymmetry of the I-V characteristics with respect to the applied voltages was caused by an asymmetry of the barrier structure caused by the polarization charges at the heterointerfaces in the DB region. 16,17 These charges also led to NDR for one bias polarity and not for the opposite one, in harmony with the theory 17 and our observations. 7,8 Figure 4 inset displays the simulated 12 schematic conduction band diagram of DB active layer.…”
Section: -2supporting
confidence: 92%
“…The observed asymmetry of the I-V characteristics with respect to the applied voltages was caused by an asymmetry of the barrier structure caused by the polarization charges at the heterointerfaces in the DB region. 16,17 These charges also led to NDR for one bias polarity and not for the opposite one, in harmony with the theory 17 and our observations. 7,8 Figure 4 inset displays the simulated 12 schematic conduction band diagram of DB active layer.…”
Section: -2supporting
confidence: 92%
“…This modiÿes considerably the potential proÿle of the double barrier structure. To understand the e ect of polarisation charges on the potential proÿle of the RTD structures, self-consistent simulations of the conduction band proÿle were obtained using a model based on real-time tight-binding Green's functions [5], the details will be published elsewhere. This model suggests that a resonance will only be observed in reverse bias when the occupied states in the emitter layer coincide with the energy of the ÿrst excited quasi-bound level in the quantum well, because the ground state in the QW is located below the Fermi level in the emitter.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kikuchi et al, have reported resonant tunnelling in GaN/AlGaN double barrier resonant tunnelling diodes (RTDs) [1][2][3] and theoretical models for resonant behaviour in such structures have been discussed [4,5]. However, Kikuchi et al, concluded that this was conventional resonant tunnelling behaviour based on measurements in one direction of current-voltage (I (V )) sweep only [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Such internal electric fields can lead to highly asymmetric I-V characteristics. 21,22 Thus, one way to improve the NDR characteristics of DB RTDs is by minimizing these polarization fields by growing the RTDs on nonpolar substrate orientations. The recent commercial availability of low dislocation density (10 6 cm -2 ) nonpolar m-plane orientation FS-GaN substrates 6 enables studying the effects of polarization on the NDR of low Al content (10%) DB RTDs.…”
Section: Effect Of Polarization Ndr Charactristics Of Db Rtdmentioning
confidence: 99%